Methionine in Poultry Nutrition: A Review - Babazadeh, Daryoush; Ahmadi Simab, Pouria (Journal of World’s Poultry Science, 2022)
Methionine is an essential amino acid which is commonly used as a supplement in poultry diets. Multiple systems are involved in the absorption and transportation of liquid and powder Methionine in the segment of the jejunum. Methionine supplementation in a low-protein diet alleviates the negative effects of heat stress and improves the performance of chickens. The supplementation of the synthetic Methionine improves the amino acid balance and consequently promotes growth performance by enhancing quantity and quality of egg production, feed efficiency, and protein synthesis, as well as decreasing fat synthesis in poultry breeds (Broiler Chicken, Laying hen, Turkey, Duck, Guinea fowl, Quail breeder, and Gees). Methionine supplementation also improves the immune response through the direct effects on protein synthesis and breakdown and indirect effects on the derivatives of Methionine. The variables, such as growing period, type of production, sex, and breed, influence the Methionine requirement. Moreover, the Methionine requirement expressed as a percentage of diet declines during the starter and grower phases.